Final remedy of the excitation in the analysis of open planar circuits - Balik, Hasan H. (My University, 2003)
The Spectral Domain Method (SDM) is widely applied to analyse planar microwave circuits, but open planar circuit analysis with SDM requires an efficient excitation modeling technique. Recent excitation modeling technique is very efficient but needs an improvement at low frequencies. This paper introduces an interpolation technique to improve the deficiency of the recent excitation modelling at low frequencies.
Keywords: Antennas; Excitation; Interpolation; Planar circuits; Spectral Domain Method (SDM)